2017
DOI: 10.1093/pcp/pcx102
|View full text |Cite
|
Sign up to set email alerts
|

Auxin Response Dynamics During Wild-Type and entire Flower Development in Tomato

Abstract: The plant hormone auxin is a major regulator of plant development and response to environmental cues. Auxin plays a particularly central role in flower development, but the knowledge of its role of flower development in crop plants with fleshy fruits, such as tomato, is still scarce. Mutations in the Aux/IAA gene ENTIRE/Indole Acetic Acid 9 (E/IAA9) lead to the precocious development of young gynoecia into parthenocarpic fruits. Here, we compared the distribution of the auxin response sensor DR5::VENUS and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 54 publications
1
42
0
Order By: Relevance
“…Auxin also regulates floral organ initiation, identity, and patterning (Reinhardt et al, 2000;Cheng et al, 2006;Kaufmann et al, 2009). Accordingly, in tomato flower, an auxin response signal has been observed in all the floral whorls during early bud development and later became prominent in the male and female reproductive organs (Goldental-Cohen et al, 2017). The abnormal floral organ patterning displayed by the CR-slmir160a mutants indicated that sly-miR160a is required also for these auxin-dependent processes.…”
Section: Discussionmentioning
confidence: 99%
“…Auxin also regulates floral organ initiation, identity, and patterning (Reinhardt et al, 2000;Cheng et al, 2006;Kaufmann et al, 2009). Accordingly, in tomato flower, an auxin response signal has been observed in all the floral whorls during early bud development and later became prominent in the male and female reproductive organs (Goldental-Cohen et al, 2017). The abnormal floral organ patterning displayed by the CR-slmir160a mutants indicated that sly-miR160a is required also for these auxin-dependent processes.…”
Section: Discussionmentioning
confidence: 99%
“…A tight communication between different female reproductive tissues as well as between female and male reproductive organs is essential to allow successful fertilization and subsequent development and growth of embryos, seed and fruit. Although, auxin has been implicated in the coordination of these transition events in different species ( Dorcey et al, 2009 ; Fuentes and Vivian-Smith, 2009 ; Figueiredo et al, 2016 ; Goldental-Cohen et al, 2017 ), the spatiotemporal details, as well as the identity of the main framework for regulatory processes have largely remained elusive. Here we present a first map of auxin biosynthesis, transport, conjugation and sensing shortly before as well as after fertilization in the model plant Arabidopsis ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic change of endogenous IAA has been proved to induce plant SE and improved SE competency [58]. Auxin/Indole-3-Acetic Acids (Aux/IAAs), Gretchen Hagen3s (GH3s), small auxin upregulated RNAs (SAURs) and auxin response factor (ARF) have been identi ed as auxin-responsive genes in auxin signaling and homeostasis [59][60][61], can regulate downstream genes precisely and rapidly, and further regulated plant growth and developmental processes. Aux/IAA family play a key role in inhibiting the expression levels of genes transcriptional activated by ARFs [62,63].…”
Section: Discussionmentioning
confidence: 99%